Religious Freedom in the Indonesian Constitution (a Democratic-Constitutional Approach) - Abu Hafsin (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
-Indonesia constitutionally is not a religiously based state, in the sense that the state does not adhere to only one religious conviction like Saudi Arabia, Pakistan or Iran. Indonesia does not support any given religious conviction as being the state’s ideology. In order to become a national policy, a given religious norm must follow “the rule of game” written in the Indonesian Constitution (UUD 45). This is important for the sake of seeking constitutional justification. Thus, knowing the position of a given religious conviction in the context of the Indonesian Constitution (UUD 45) is of great importance. The following discussion will be devoted to elaborating the constitutional arguments with democratic approach. Key words: Indonesian Constitution, state, citizen, absolutism